Implementation of an AI-Based Project-Based Learning Model to Enhance Student Learning Motivation in Productive Digital Business Subjects at SMK As Salafi Balung - Hilmiyah, Arifatul; Wijaya, Shendy Andrie; Cahyono, Arie Eko (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to enhance students' learning motivation through an Artificial Intelligence (AI)-based Project-Based Learning (PjBL) model in the Digital Business subject at SMK As-Salafi Balung. The problem addressed is the low level of motivation caused by conventional methods that provide minimal active and contextual engagement, leading to reduced enthusiasm and limited understanding of the relevance of learning materials to the digital work environment. The general objective is to improve the quality of the learning process to be more adaptive to digital technology development. Specific objectives include: (1) increasing students' motivation through AI-based PjBL; (2) evaluating the improvement of non-cognitive learning outcomes, particularly critical thinking and digital technology skills for real-world projects; and (3) presenting innovative strategies aligned with industry demands. This research uses a qualitative approach with Classroom Action Research (CAR) based on the Kemmis & McTaggart model, conducted in two cycles. Data were collected through observation, interviews, and documentation to assess motivation and attitudinal changes. The study expects to produce a contextual AI-integrated PjBL model to enhance motivation and 21st-century skills.